Characterization and translational development of IOA-289, a novel autotaxin inhibitor for the treatment of solid tumors - Deken, M.A.; Niewola-Staszkowska, K.; Peyruchaud, O.; Mikulčić, N.; Antolić, M.; Shah, P.; Cheasty, A.; Tagliavini, A.; Nizzardo, A.; Pergher, M.; Ziviani, L.; Milleri, S.; et al. (Immuno-oncology technology, 2023)
Autotaxin-lysophosphatidic acid (ATX-LPA) signaling has a predominant role in immunological and fibrotic processes, including cancer. Several ATX inhibitors and LPA receptor antagonists have been clinically evaluated, but none in patients with solid tumors. Many cancers are burdened with a high degree of fibrosis and an immune desert phenotype (so-called ‘cold’ tumors). In these cold tumors, the fibrotic stroma provides an intrinsic cancer-supporting mechanism. Furthermore, the stroma prevents penetration and limits the effectiveness of existing therapies. IOA-289 is a novel ATX inhibitor with a unique chemical structure, excellent potency and an attractive safety profile. In vitro and in vivo pharmacology studies have been carried out to elucidate the pharmaceutical properties and mechanism of action of IOA-289. A phase I clinical study in healthy volunteers was carried out to determine the pharmacokinetics and pharmacodynamics of IOA-289 following a single oral dose. In vitro and in vivo studies showed that IOA-289 is a potent inhibitor of ATX and, as a monotherapy, is able to slow progression of lung fibrosis and tumor growth in mouse models. In a clinical study, IOA-289 showed a dose-dependent increase in plasma exposure levels and a corresponding decrease in circulating LPA. Our data show that IOA-289 is a novel ATX inhibitor with a unique chemical structure, excellent potency and an attractive safety profile. Our data support the further development of IOA-289 as a novel therapeutic approach for the treatment of cancer, particularly those with a high fibrotic and immunologically cold phenotype. •IOA-289 is a novel, first-in-class inhibitor of autotaxin with a unique binding mode.•IOA-289 inhibits biomarkers of fibrosis and shows efficacy in an in vivo lung fibrosis and cancer models.•We demonstrate that ATX inhibition has three mechanisms relevant for the treatment of cancer.•We describe the preclinical studies supporting the transition of IOA-289 into a clinical trial.•The pharmacokinetic/pharmacodynamic relationship of IOA-289 with circulating LPA in healthy human subjects is disclosed.